PENGARUH PEMBERIAN JUS BELIMBING TERHADAP PENURUNAN TEKANAN DARAH PADA LANSIA PENDERITA HIPERTENSI DI KELURAHAN TIMBANGAN KOTA PADANGSIDIMPUAN - Daulay, Nanda Masraini; Siregar, Lisda Yanti; Situmeang, Tiodora (Universitas Aufa Royhan, 2016)
Hypertension or high blood pressure is an increase in systolic blood pressure over 140 mmHg and disatolic more than 90 mmHg. Hypertension therapy are pharmacologically there are drugs there are also non-pharmacological ie diet, exercise or administration of starfruit juice. The purpose of this study was to determine the effect of starfruit juice to the reduction of blood pressure in patients with hypertension. This research method is quasy experiment with non equivalent control group design. This research was conducted in the Timbangan Village of Padangsidimpuan City against 28 people, with 14 in the experimental group and 14 control group consisted of male and female. The experimental group received 200 ml starfruit juice for 7 days. The results of the experimental group the majority of blood pressure lightweight category 13 respondents (92.9%) and the results of blood pressure control group lightweight category 8 majority of respondents (57.1%). Test test for normality using independent t test. The results showed a significant influence on the reduction of blood pressure in patients with hypertension after being given starfruit juice (p = 0.029). Starfruit juice consumption of 200 ml for 7 days can lower the blood pressure of hypertensive patients, both men and women.